Making Aromatherapy Candles with Natural Ingredients from Essential Oils and Soybean Oil - Syaifullah Muhammad; M. Dirhamsyah; Ernawati Ernawati; Raihan Dara Lufika; Sabrina Khairunnisa; Nanda Funna Ledita (Universitas Syiah Kuala, 2022)
Relaxation is considered as a process that relieves stress on your mind and body. At the present, there are many different forms of relaxation and aromatherapy. One of the important products to be developed further is aromatherapy candles. However, candles on the market generally still use materials that are not environmentally friendly such as paraffin. So this study aims to making aromatherapy candle using natural ingredients from essential oils and soybean oil. Soybean oil (Soy wax) is a potential substitute for paraffin which is biodegradable, renewable and friendly environment. This study also uses patchouli oil, peppermint oil and lemon oil which have benefits for anti-depressant, relieve pain and for immune system. The aromatherapy candle materials consist of : soy wax, essential oils, dyes, candle wick and candle glass. The research stage was started by developing the aromatherapy candle formulas, establishing the working procedures, and conducting quality testing, involve test the preference for the smell of candles before and after burning, burn time test, test for the overall appearance of the candle, visual test colour preferences and therapeutic effect. The research revealed that the aromatherapy candle 1) 73,3% respondent agree the aroma of the candle more preferable when the candle was burned compared to unburned candle; 2) have burn time ranged from 8 hours 14 minutes to 10 hours 20 minutes; 3) 93.3% of respondents like and really like the texture and visual of the candle, based on SNI 0386-1989-A/II 0348-1980, the physical condition of a good candle is to have the same and even colour, not cracked, not deformed and not broken; 4) 80% respondent like and really like the colour of the candle; 5) 93.3% respondent agree and strongly agree that the aroma of candles has a good therapeutic effect for provide a calm, comfortable effect and can improve mood.